Analisis Profil Keterampilan Kolaborasi Mahasiswa Menggunakan Model Team Based Project pada Mata Kuliah Kimia Umum - Rasyid, Muhamad Al; Yulita, Inelda; Sabekti, Ardi Widhia; Fitriani, Rita (Universitas Negeri Padang, 2025)
Collaborative skills of students in the lecture process are still not optimal, whereas collaboration skills are the main skills that must be possessed by students in an effort to become quality individuals. This study aims to analyze the collaboration skills of students of the Biology Education undergraduate study program using the team-based project model. The research method used is descriptive quantitative. The subjects in the study were 40 first-semester Biology Education undergraduate students using the total sampling technique. The data collection method used was by distributing a collaboration skills questionnaire via googleforms. The questionnaire distributed contained 9 aspects of collaboration skills. The results of this study are the average percentage of skill indicators including, 1) positive collaboration interdependence of 87.80%; 2) face-to-face interaction of 69.37%; 3) personal responsibility of 88.75%; 4) communication skills of 90.62%; and 5) group work skills of 85.62%. So overall the collaboration skills of students who apply the team-based project model are included in the very good category.